2021
DOI: 10.3390/plants10081608
|View full text |Cite
|
Sign up to set email alerts
|

Response of Normal and Low-Phytate Genotypes of Pea (Pisum sativum L.) on Phosphorus Foliar Fertilization

Abstract: Phosphorus (P) is an important nutrient in plant nutrition. Its absorption by plants from the soil is influenced by many factors. Therefore, a foliar application of this nutrient could be utilized for the optimal nutrition state of plants. The premise of the study is that foliar application of phosphorus will increase the yield of normal-phytate (npa) cultivars (CDC Bronco a Cutlass) and low-phytate (lpa) lines (1-2347-144, 1-150-81) grown in soils with low phosphorus supply and affect seed quality depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Moreover, this study found that P application improved flax seed yield, which is consistent with previous reports ( Muhammad et al., 2020 ; Xie et al., 2020 ; Xie et al., 2022 ). Similar results have been observed in other species, such as soybean ( Yin et al., 2016 ; Taliman et al., 2019 ), pea, canola ( Yin et al., 2016 ), wheat ( Škarpa et al., 2021 ), maize ( Škarpa et al., 2021 ), and rice ( Škarpa et al., 2021 ). In this study, the application of P fertilizer had a significant influence on both 1000-seed weight and the number of capsules per plant in flax, which is consistent with previous research findings ( Hocking and Pinkerton, 1993 ; Xie et al., 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, this study found that P application improved flax seed yield, which is consistent with previous reports ( Muhammad et al., 2020 ; Xie et al., 2020 ; Xie et al., 2022 ). Similar results have been observed in other species, such as soybean ( Yin et al., 2016 ; Taliman et al., 2019 ), pea, canola ( Yin et al., 2016 ), wheat ( Škarpa et al., 2021 ), maize ( Škarpa et al., 2021 ), and rice ( Škarpa et al., 2021 ). In this study, the application of P fertilizer had a significant influence on both 1000-seed weight and the number of capsules per plant in flax, which is consistent with previous research findings ( Hocking and Pinkerton, 1993 ; Xie et al., 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Pea varieties respond differently to fertilization [ 23 , 28 ] and environmental conditions [ 2 ]. The main traits that determine the level of adaptability in peas are a high harvest index, good ripening, disease resistance, resistance to shatter, high potential yield, seed weight, and seed number per pod [ 25 , 29 ]. In this study, the variety Ieva DS demonstrated the greatest adaptability and the ability to produce the highest seed yield of all studied varieties, regardless of the weather conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus, for example, is a vital element for all plants, as it is essential for growth, photosynthesis, protein structure, and the formation of nodules for flow formation, among others. [ 87 ]. In cereals and legumes, the primary storage form of phosphorus is in the form of phytic acid.…”
Section: Bionanotechnology and Agriculturementioning
confidence: 99%